OCCURRENCE OF SOMATIC OBJECTS IN PAREMIOLOGICAL TEXTS IN ENGLISH AND UZBEK LANGUAGES - Zokirova Dilsora Zokhiddin kizi (Modern American Journals, 2025)
This article examines the occurrence and role of somatic objects—terms referring to body parts—in English and Uzbek proverbs. Based on the theory of conceptual metaphor, the study analyzes how both languages use bodily metaphors to convey thoughts, emotions, behaviors, and social values. The findings reveal that although there are universal metaphorical structures, cultural interpretations differ: English proverbs often highlight individualism and rationality, while Uzbek proverbs emphasize respect, community, and emotional sincerity. This research contributes to cross-cultural linguistics by revealing how language, through somatic imagery, reflects cultural identity.
Keywords: Somatic objects, proverbs, conceptual metaphor, paremiology, cultural comparison, English, Uzbek